Next-Generation Ultrasol Curcumin Boosts Muscle Endurance and Reduces Muscle Damage in Treadmill-Exhausted Rats - Sahin, Emre; Orhan, Cemal; Erten, Fusun; Er, Besir; Acharya, Manutosh; Morde, Abhijeet A.; Şahin, Kazım (Mdpi, 2021)
Curcumin positively affects performance during exercise and subsequent recovery. However, curcumin has limited bioavailability unless consumed in larger doses. In the current study, we examined the impact of a new formulation of curcumin, Next-Generation Ultrasol Curcumin (NGUC), which is relatively more bioavailable than natural curcumin on exhaustion time, grip strength, muscle damage parameters, and serum and muscle proteins. A total of 28 rats were randomly grouped as control (C, non-supplemented), exercise (E, non-supplemented), E+NGUC100 (supplemented with 100 mg/kg BW NGUC), and E+NGUC200 (supplemented with 200 mg/kg NGUC). Grip strength and exhaustion time were increased with NGUC supplementation (p < 0.0001). Creatine kinase (CK), lactate dehydrogenase (LDH), lactic acid (LA), myoglobin, malondialdehyde (MDA) concentrations were reduced in serum, and muscle tissue in NGUC supplemented groups (p < 0.05). In contrast, NGUC supplementation elevated the antioxidant enzyme levels compared to the non-supplemented exercise group (p < 0.01). Additionally, inflammatory cytokines were inhibited with NGUC administration (p < 0.05). NGUC decreased PGC-1 alpha, p-4E-BP1, p-mTOR, MAFbx, and MuRF1 proteins in muscle tissue (p < 0.05). These results indicate that NGUC boosts exercise performance while reducing muscle damage by targeting antioxidant, anti-inflammatory, and muscle mass regulatory pathways.
Keywords: curcumin; exhaustion; inflammation; antioxidant; exercise